(untitled) (Economics and region, 2022)
The article is devoted to the study of domestic and foreign experience in the implementation of youth policy. The basic conceptual principles of implementation of domestic and foreign experience in the implementation of youth policy are presented. It is established that the youth policy of Ukraine is in a state of formation. It is determined that the main factors of low socio-political activity of young people in Ukraine are: low political consciousness (in terms of participation in elections and membership in political parties); low level of involvement in the activities of public organizations; low level of participation in volunteer movements; migration sentiments to leave their communities. It is established that solving the problem of low socio-political activity of youth should be a priority at the present stage of development of the state youth policy both at the central and community levels.